2024
DOI: 10.1007/s10695-024-01314-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of diets containing Hermetia illucens meal on the growth, intestinal health, and microbiota of gilthead seabream (Sparus aurata)

Simona Rimoldi,
Ambra Rita Di Rosa,
Marianna Oteri
et al.

Abstract: The present study investigated the effect of replacing fishmeal (FM) with insect meal of Hermetia illucens (HI) in the diet of Sparus aurata farmed inshore on growth, gut health, and microbiota composition. Two isolipidic (18% as fed) and isoproteic (42% as fed) diets were tested at the farm scale: a control diet without HI meal and an experimental diet with 11% HI meal replacing FM. At the end of the 25-week feeding trial, final body weight, specific growth rate, feed conversion rate, and hepatosomatic index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 96 publications
1
3
0
Order By: Relevance
“…The comparison of microbial profiles in the gut of PM20 and PM25 fish showed a positive association of the genus Paenibacillus with insect meal. This result confirmed what was previously reported in rainbow trout and gilthead seabream in response to dietary H. illucens meal ingestion [34,35,53]. In contrast, Rangel et al [52] found that consumption of diets enriched with H. illucens exuviae, but not insect meal, led to an increase in the genus Paenibacillus in the gut of European seabass.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The comparison of microbial profiles in the gut of PM20 and PM25 fish showed a positive association of the genus Paenibacillus with insect meal. This result confirmed what was previously reported in rainbow trout and gilthead seabream in response to dietary H. illucens meal ingestion [34,35,53]. In contrast, Rangel et al [52] found that consumption of diets enriched with H. illucens exuviae, but not insect meal, led to an increase in the genus Paenibacillus in the gut of European seabass.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast to the exuviae meal, the amount of insect meal was not sufficient to attenuate the negative effects of PBM on the abundance of lactic acid bacteria. Similarly, in gilthead seabream, a 10% content of H. illucens meal was not sufficient to increase the abundance of lactic acid bacteria in the gut [34,53].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations